Três ensaios sobre a dengue no município de Pedro Leopoldo: um estudo sobre o LIRAa - Lucas Resende de Carvalho (2023)
Dengue fever has been endemic in Brazil for decades, and its primary vector is the Aedes aegypti mosquito. Aedes development is predominantly urban, in the interior of breeding habitats created by human action. In Brazil, the tool used as a guide for control measures since 2003 is the Rapid Survey of Indices for Aedes aegypti (LIRAa). LIRAa is the primary public policy for monitoring the vector and is mandatory in municipalities with more than 2,000 properties. The three articles in this thesis are inserted in this context, using georeferenced home visit data from LIRAa in Pedro Leopoldo/MG between 2015 and 2018. The first article estimates the socio-spatial determinants for the occurrence of mosquito breeding sites in households. The second article aims to evaluate the capacity of LIRAa to forecast dengue epidemics. Finally, the last article calculates the economic burden of dengue for the municipality of Pedro Leopoldo, highlighting the costs related to the execution of LIRAa.